Functional MRI using Fourier decomposition of lung signal: reproducibility of ventilation- and perfusion-weighted imaging in healthy volunteers - Lederlin, Mathieu; Bauman, Grzegorz; Eichinger, Monika; Dinkel, Julien; Brault, Mathilde; Biederer, Jürgen; Puderbach, Michael (European journal of radiology, 2013)
Purpose - To assess the reproducibility of Fourier decomposition (FD) based ventilation- and perfusion-weighted lung MRI. - Methods - Sixteen healthy volunteers were examined on a 1.5 T whole-body MR-scanner with 4-6 sets of coronal slices over the chest volume with a non-contrast enhanced steady-state free precession sequence. The identical protocol was repeated after 24h. Reconstructed perfusion- and ventilation-weighted images were obtained through non-rigid registration and FD post-processing of images. Analysis of signal in segmented regions of interest was performed for both native and post-processed data. Two blinded chest radiologists rated image quality of perfusion- and ventilation-weighted images using a 3-point scale. - Results - Reproducibility of signal between the two time points was very good with intra-class correlation coefficients of 0.98, 0.94 and 0.86 for native, perfusion- and ventilation-weighted images, respectively. Perfusion- and ventilation-weighted images were of overall good quality with proportions of diagnostic images of 87-95% and 69-75%, respectively. Lung signal decreased from posterior to anterior slices with image quality of ventilation-weighted images in anterior areas rated worse than in posterior or perfusion-weighted images. Inter- and intra-observer agreement of image quality was good for perfusion and ventilation. - Conclusions - The study demonstrates high reproducibility of ventilation- and perfusion-weighted FD lung MRI.